CHILDREN’S PRODUCTION OF THEIR HERITAGE LANGUAGE AND MULTILINGUALISM - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2011)
ABSTRACT Children are very unique. They can learn more than one languages at very young age. They have ability to do it since the brain is very active in absorbing kinds of languages through the work of neuron. It is a sign that young learners can be bilingual or multilingual children. They will learn languages from their milieu and society around them. If they are exposed since they were toddlers, the result will be good as their brain still developed within their golden period. They even can maintain their heritage language with the help of society while they are learning another new language. It helps them to communicate to their peer and adult properly. By participating in social and cultural practice children acquire the linguistic and cognitive orientation of their elders. Children who have the opportunity to learn multiple languages from early childhood and to maintain them throughout their lives are fortunate indeed, and families that can offer this opportunity to their children should be encouraged to do so. Key words: neuron, bilingual, multilingual